Uji Konsentrasi Larutan Ekstrak Tauge Terhadap Viabilitas Benih Tiga Varietas Padi - Rahmawati Rahmawati; Hairu Suparto; Muhammad Imam Nugraha (Universitas Lambung Mangkurat, 2022)
Rice (Oryza sativa L.) is an agricultural crop and is the world's main crop. In general, farmers use local varieties of rice seeds with a relatively long shelf life, causing seed deterioration and resulting in a decrease in seed viability. One way to increase the viability of local varieties of rice seeds is by adding organic matter from the bean sprout extract solution. The purpose of this study was to determine the interaction between varieties and the concentration of bean sprout extract solution on the viability of rice seeds and to determine the concentration and effect of giving the best bean sprout extract solution to the viability of rice seeds. This research was carried out from June to July 2021 at the Production Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University. The experimental method used in this study was a Randomized Block Design (RAK) with 2 factorial factors, namely rice variety (V) and bean sprout extract concentration (K). The first factor is rice variety (V) which consists of 3 types of rice, namely V1 (Inpari30), V2 (Balimau) and V3 (Siam Epang) and the second factor is the concentration of bean sprout extract solution (K) which consists of 3 treatments, namely K1 (10 %), K2 (20%) and K3 (30%). The results showed that the interaction of soaking rice seeds in a solution of bean sprout extract and rice varieties had a significant effect on growth potential, germination and growth simultaneously. In the growth speed, only single factor concentration of bean sprout extract solution and variety had a significant effect. Soaking the seeds in a solution of bean sprout extract with a concentration of 10% on the Siam Epang rice variety (K1V3) was the best treatment and was able to increase growth potential, germination and growth simultaneously. Soaking seeds at 10% concentration of bean sprout extract solution and Siam Epang variety was the best single factor treatment for growth speed. Copyright ã 2020 Agroekotek View. All rights reserved. Keywords: Local varieties of rice; Viability; Bean sprout extract solution.